Comparison Between 30-15 Intermittent Fitness Test and Multistage Field Test on Physiological Responses in Wheelchair Basketball Players - Weissland, Thierry; Faupin, Arnaud; Borel, Benoit; Leprêtre, Pierre-Marie (Frontiers in Physiology, 2015)
The intermittent nature of wheelchair court sports suggests using a similar protocol to assess repeated shuttles and recovery abilities. This study aimed to compare performances, physiological responses and perceived rating exertion obtained from the continuous multistage field test (MFT) and the 30-15 intermittent field test (30-15IFT). Eighteen trained wheelchair basketball players (WBP) (WBP: 32.0±5.7y, IWBF classification: 2.9±1.1points) performed both incremental field tests in randomized order. Time to exhaustion, maximal rolling velocity (MRV), VO2peak and the peak values of minute ventilation (VEpeak), respiratory frequency (RF) and heart rate (HRpeak) were measured throughout both tests; peak and net blood lactate (Δ [Lact-] = peak–rest values) and perceived rating exertion (RPE) values at the end of each exercise. No significant difference in VO2peak, VEpeak and RF was found between both tests. 30-15IFT was shorter (12.4±2.4 vs. 14.9±5.1min, P<0.05) but induced higher values of MRV and Δ [Lact-] compared to MFT (14.2±1.8 vs. 11.1±1.9km•h-1 and 8.3±4.2 vs. 6.9±3.3mmol•L-1, P<0.05). However, HRpeak and RPE values were higher during MFT than 30-15IFT (172.8±14.0 vs. 166.8±13.8bpm and 15.3±3.8 vs.13.8±3.5, respectively, P<0.05). The intermittent shuttles intercepted with rest period occurred during the 30-15IFT could explain a greater anaerobic solicitation. The higher HR and overall RPE values measured at the end of MFT could be explained by its longer duration and a continuous load stress compared to 30-15IFT. In conclusion, 30-15IFT has some advantages over MFT for assess in addition physical fitness and technical performance in WBP.